Biosynthesis of poly(2‐hydroxyisovalerate‐co‐lactate) by metabolically engineered Escherichia coli. Issue 12 (27th September 2016) - Yang, Jung Eun; Kim, Je Woong; Oh, Young Hoon; Choi, So Young; Lee, Hyuk; Park, A‐Reum; Shin, Jihoon; Park, Si Jae; Lee, Sang Yup
Abstract: Polyhydroxyalkanoates (PHAs) containing 2‐hydroxyacids such as lactate (LA) and 2‐hydroxybutyrate (2HB) have recently been produced by metabolically engineered microorganisms. Here, we further expanded 2‐hydroxyacid monomer spectrum of PHAs by engineering Escherichia coli to produce PHAs containing 2‐hydroxyisovalerate (2HIV). To generate 2HIV in vivo, feedback resistant ilvBN mut genes encoding acetohydroxyacid synthase and ilvCD genes encoding ketol‐acid reductoisomerase and dihydroxyacid dehydratase, respectively, and panE gene encodingd ‐2‐hydroxyacid dehydrogenase are overexpressed. Also, pct540 gene encoding evolved propionyl‐CoA transferase and phaC1437 gene encoding evolved PHA synthase are overexpressed along with ilvBN mut, ilvCD, and panE genes in E. coli strain for in vivo synthesis of 2HIV containing PHAs. E. coli strain expressing all of these genes can produce poly(13.2 mol% 2HIV‐ co ‐7.5 mol% 2HB‐ co ‐42.5 mol% 3HB‐ co ‐36.8 mol% LA) when it is cultured in a chemically defined medium containing 20 g/L of glucose and 2 g/L of sodium 3‐hydroxybutyrate (3HB). To produce PHA containing only 2HIV and LA monomers, poxB, pflB, adhE and frdB genes encoding enzymes involved in competing pathways for pyruvate are deleted so that cells can generate more 2HIV and LA. When this engineered E. coli strain expressing ilvBN mut, ilvCD, panE, pct540 and phaC1437 genes is cultured in the medium containing 20 g/L of glucose and 2 mMl ‐isoleucine, which can inhibitl ‐threonine dehydratase responsible for in vivo 2HB generation, poly(20 mol% 2HIV‐ co ‐80 mol% LA) can be produced to the polymer content of 9.6% w/w. These results suggest that novel PHAs containing 2HIV can be produced by engineering branched‐chain amino acid metabolism. Abstract : Poly(2‐hydroxyisovalerate‐ co ‐lactate) has potential to be used as raw materials for biomedical applications. Metabolically engineered Escherichia coli strains able to efficiently synthesize poly(2‐hydroxyisovalerate‐ co ‐lactate) by engineering branched‐chain amino acid metabolic pathways to support more 2‐ketoisovalerate, important precursor for 2‐hydroxyisovalerate, from glucose are developed.